Water Hyacinth (eichhornia crassipe) as compost and enriched mulch - Siti Fatimah Ismail (2013)
Water hyacinth (Eichhornia crassipes). has attracted significant attention as the world's worst invasive aquatic plant due to its extremely rapid proliferation, presenting serious challenges in irrigation and power generation. To utilize this agro-waste material and convert E. crassipes into useful product by turn it into compost and mulch. Six attributes were studied in I. javanica site included the soil pH value, soil moisture content, effectiveness of weeds suppression, bud growth and flowering before and after the application of the treatment. Result shows significant improvement in the soil pH, soil moisture content value and effectiveness in weeds suppression at I. javanica site compared to the untreated area using compost and mulch by compressed and non-the the treatment showed not significantly different on the compressed (p<0.05). Howe , bud growth and flowering of I. javanica (p>0.05). The best enrichment proportion for flowering and bud growth of I. javanica was N,P,K 5:10:5.